Maternal-fetal benefits of gestacional physical activity: an integrative literature revew (Research, Society and Development, 2022)
Objective: to carry out a careful reading of the existing literature on pregnancy-related changes and the benefits that physical activity provides during this period, thus contributing to future studies in the area and helping to improve the quality of life of pregnant women and children. Method: This is a descriptive study of the integrative literature review type, which sought to answer which are the maternal-fetal benefits with the practice of physical activity during pregnancy. The search was conducted in the online databases National Scientific Electronic Library Online (Scielo) and Google Scholar, from October to November 2022. Result: Six important aspects of the literature were highlighted in the study - changes necessary for gestational development; harm of excessive weight gain during pregnancy; sociodemographic profile of pregnant women and how this interferes with the high rates of sedentary lifestyle during pregnancy; benefits for mother and baby when practicing physical activity during pregnancy; risks and contraindications that health professionals encounter when recommending physical activity; important recommendations to improve the rates of active pregnant women with the help of health professionals. Conclusion: the gestational success depends directly on healthy habits, considering that physical activity does not show risks to the health of pregnant women without contraindications, on the contrary, it helps to reduce various complications and maternal-fetal pathologies.